(untitled) (Journal of Social Sciences Review, 2021)
This paper investigated principals’ leadership styles and students’ academic achievement in secondary level in Dir Upper, KP. The co-relational research design was used for the study. The study population comprised all the 64 secondary schools in the district. Out of total 32 secondary schools were selected through the simple random sampling techniques. Out of the total 64 principals, 32 were selected for this work using a stratified random sampling technique. For the data collection questionnaire was used. The collected data were analyzed by using different statistical tools. The study result revealed that the democratic leadership style was the common leadership style adopted by secondary school principals in the area. Similarly, it was found that autocratic leadership style significantly associated with students’ academic performance. It was recommended that principals should make use of autocratic leadership style in order to improve academic achievement of students in their respective schools.